2021
DOI: 10.1248/bpb.b21-00078
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Pressure Stress Reduces Interleukin-1β-Induced Cyclooxygenase-2 Expression in Cultured Rat Vascular Smooth Muscle Cells

Abstract: Elevated mechanical stress on blood vessels associated with hypertension has a direct effect on the function of vascular endothelial cells and vascular smooth muscle cells (VSMCs).In the present study, we have identified the effect of pulsatile pressure stress on cyclooxygenase-2 (COX-2) expression induced by interleukin (IL)-1β in cultured rat VSMCs. VSMCs were isolated from aortic media of Wistar rats and cultured. Pulsatile pressure applied to VSMCs was repeatedly given between either 80 and 160 mmHg, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Protein expression and phosphorylation were evaluated by Western blot analysis as previously described [ 19 ]. The cells were washed with ice-cold phosphate-buffered saline, and whole cell lysates were prepared in a mammalian protein extraction buffer (GE Healthcare Life Sciences, Buckinghamshire, UK) containing a protease inhibitor mix (GE Healthcare Life Sciences).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Protein expression and phosphorylation were evaluated by Western blot analysis as previously described [ 19 ]. The cells were washed with ice-cold phosphate-buffered saline, and whole cell lysates were prepared in a mammalian protein extraction buffer (GE Healthcare Life Sciences, Buckinghamshire, UK) containing a protease inhibitor mix (GE Healthcare Life Sciences).…”
Section: Methodsmentioning
confidence: 99%
“…We previously developed a pressure-loading apparatus that can apply arbitrary pressure to cultured cells [ [16] , [17] , [18] ]. Using this apparatus, we found that applying pulsatile pressure stress between 80 and 160 mmHg at a rate of 4 cycles/min in order to simulate systolic hypertension significantly suppresses IL-1β-induced COX-2 expression in rat aortic SMCs [ 19 ]. The inhibition of mitogen-activated protein kinase (MAPK) phosphorylation was involved in the mechanism for the pressure-induced suppression of COX-2 expression [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-1β is one of the most common proinflammatory cytokines, and as an initial factor regulating inflammation, it is considered as the most classical inflammatory regulator [39]. As a multifunctional inflammatory factor, IL-1β is crucial for fever, wound healing, inflammatory stimulation, hematopoiesis, immune response, and other physiological responses [40]. IL-6 can activate acute response proteins, play a proinflammatory role, affect the growth of fibroblasts and endothelial cells, and activate the local and systemic defense mechanisms of the host [41].…”
Section: Determination Of Serum Inflammatory Factorsmentioning
confidence: 99%
“…Our findings revealed that SDSS reduced the levels of IL-1β, IL-6, and TNF-α, thereby accelerating the healing of PU in mice. responses [40]. IL-6 can activate acute response proteins, play a proinflammatory role, affect the growth of fibroblasts and endothelial cells, and activate the local and systemic defense mechanisms of the host [41].…”
Section: Determination Of Serum Inflammatory Factorsmentioning
confidence: 99%